Dampak Kurangnya Informasi mengenai Kondisi Runway setelah Hujan terhadap Keselamatan Penerbangan - Supardam, Dhian; Fitrianti, Rachma; Nur Yulia, Sukma (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2020)
In the world of aviation, there are many aspects that support the occurrence of a safe and smooth flight to be able to connect trips between islands and even continents. When talking about flight, of course, what comes to our mind is a plane that airs regularly in the air, but to pass it through it regularly requires a guide which ensures flight activities in a smooth and safe condition. An air traffic controller or air traffic controller (ATC) is a person who ensures and guides the aircraft while it is on the ground or it is in the airborne, the ATC is also tasked with providing information needed by the pilot, such as weather information, flight navigation, and air traffic. And guide the pilot to raise, lower, or turn the plane. ATC must be ready to guide the aircraft even in hot or rainy weather. Rainy weather conditions can greatly affect flight activities, this is caused by runways that are the main thing in an airport. The runway is used for taking off and landing an aircraft. If it rains, the runway conditions will be wet and when the runway is wet, there is a high risk of aircraft activities, especially if there is standing water on the runway. which is currently not available at El Tari airport, Kupang. The tool is used to provide information about water levels on the runway.